Aba-Carina P. (2019) Intersemiotic Translation Literary and Linguistic Multimodality. Cham: Springer Nature Switzerland AG - Čemerin, Vedrana (Transletters. International Journal of Translation and Interpreting, 2020)
This review examines Aba-Carina Pârlog’s volume on the theoretical and practical aspects of intersemiotic translation, with a purposeful focus on multimodality at its core. While somewhat compressed in length, at 80 pages in total, the book draws on the wealth of semiotic and translatological literature and presents its main points effortlessly and with a precision sometimes lacking in drawn-out academic treatises on related topical issues. The author explores and illustrates each of their themes in an approachable and thorough manner, building their arguments on practical examples for each theoretical question.